Microbial mechanisms of carbon sequestration discrepancy between broadleaf and Moso bamboo forests - Xu, Yaowen; Jiao, Jiejie (Frontiers in Microbiology, 2025)
In subtropical areas, broadleaf forests are being increasingly converted into Moso bamboo (Phyllostachys pubescens) forests. However, few studies have systematically compared soil organic carbon (SOC) between broadleaf and Moso bamboo forests. Therefore, we investigated SOC content and relative contributions of microbial and plant residues to SOC in broadleaf and Moso bamboo forests using biomarkers. The results show that the SOC content in Moso bamboo forest soil was 12.58% lower than that in adjacent broadleaf forest. Moreover, Moso bamboo forest soils also have less microbial-derived C but more plant-derived C compared with that in the broadleaf forest soil. The changes of microbial- and plant-derived C were mainly affected by soil properties. In particular, soil pH, ligninase/cellulase ratio, and mineral properties were the main factors regulating microbial-derived C, whereas mineral properties primarily controlled plant-derived C. Overall, our study reveals differences in C sequestration pathways between broadleaf and Moso bamboo forests, highlighting the potential to increase C storage through appropriate soil management, which provides a valuable reference for mitigating climate change.